The influence of non‐HLA antibodies directed against angiotensin II type 1 receptor (AT1R) on early renal transplant outcomes. (30th June 2014) - Banasik, Mirosław; Boratyńska, Maria; Kościelska‐Kasprzak, Katarzyna; Kamińska, Dorota; Bartoszek, Dorota; Żabińska, Marcelina; Myszka, Marta; Zmonarski, Sławomir; Protasiewicz, Marcin; Nowakowska, Beata; Hałoń, Agnieszka; Chudoba, Pawel; et al.
Summary Non‐HLA antibodies (Abs) targeting vascular receptors are thought to have an impact on renal transplant injury. Anti‐angiotensin II type 1‐receptor‐activating antibodies (anti‐AT1R) have been mentioned to stimulate a severe vascular rejection, but the pretransplant screening has not been introduced yet. The aim of our study was to assess the incidence and importance of anti‐AT1R antibodies and their influence on renal transplant in the 1st year of observation. We prospectively evaluated the presence of anti‐AT1R antibodies in 117 consecutive renal transplant recipients in pre‐ and post‐transplant screening. Anti‐AT1R antibodies were observed in 27/117 (23%) of the analyzed recipients already before transplantation. The function of renal transplant was considerably worse in anti‐AT1R(+) group. The patients with anti‐AT1R Abs >9 U/ml lost their graft more often. Biopsy‐proven AR was described in 4/27 (15%) pts in the anti‐AT1R(+) group and 13/90 (14.4%) in the anti‐AT1R(−) group, but more severe cases of Banff IIB or antibody‐mediated rejection (AMR) were more often observed in anti‐AT1R (+) 4/27 (15%) vs. 1/90 (1.1%) in anti‐AT1R(+) (P = 0.009). Patients with anti‐AT1R Abs level >9 U/ml run a higher risk of graft failure independently of classical immunological risk factors. The recipients with anti‐AT1R Abs developed more severe acute rejections described as IIB or AMR in Banff classification. More recipients among the anti‐AT1R‐positive ones lost the graft. Our study suggests monitoring of anti‐AT1R Abs before renal transplantation for assessment of immunologic risk profiles and the identification of patients highly susceptible to immunologic events, graft failure, and graft loss.